2019
DOI: 10.1155/2019/7547648
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Robot Indoor Positioning System Based on K-ELM

Abstract: Mobile Robot Indoor Positioning System has wide application in the industry and home automation field. Unfortunately, existing mobile robot indoor positioning methods often suffer from poor positioning accuracy, system instability, and need for extra installation efforts. In this paper, we propose a novel positioning system which applies the centralized positioning method into the mobile robot, in which real-time positioning is achieved via interactions between ARM and computer. We apply the Kernel extreme lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The extreme learning machine (ELM) has also been applied to indoor location fingerprinting due to its simplicity and speed [29]. Wang et al [30] used the kernel ELM (KELM) for indoor positioning of robots and showed that KELM not only has high positioning accuracy but also strong real-time performance. The [31] uses RF for position prediction and experiments show that the algorithm has a positioning accuracy of 1.68 m in 112 m 2 space.…”
Section: Fingerprint Positioning Algorithmsmentioning
confidence: 99%
“…The extreme learning machine (ELM) has also been applied to indoor location fingerprinting due to its simplicity and speed [29]. Wang et al [30] used the kernel ELM (KELM) for indoor positioning of robots and showed that KELM not only has high positioning accuracy but also strong real-time performance. The [31] uses RF for position prediction and experiments show that the algorithm has a positioning accuracy of 1.68 m in 112 m 2 space.…”
Section: Fingerprint Positioning Algorithmsmentioning
confidence: 99%
“…The In [19], the authors propose kernel ELM-(K-ELM-) based target L&T using 68,500 RSSI measurements obtained from indoor area of 32 meter × 16 meter with eight sensor nodes.…”
Section: Related Workmentioning
confidence: 99%
“…This is a time-consuming task, and thus a CNN-based localization approach may be accurate for specific system conditions but is not suitable in general. The authors in [ 23 ] proposed a RSS-based robot indoor positioning scheme based on the kernel extreme learning machine (K-ELM) algorithm. The authors took 68,500 samples of RSSI measurements for a 32 m × 16 m area using eight APs.…”
Section: Related Workmentioning
confidence: 99%